The structure of creative cognition in the human brain - Jung, Rex E.; Mead, Brittany S.; Carrasco, Jessica; Flores, Ranee A. (Frontiers in Human Neuroscience, 2013)
Creativity is a vast construct, seemingly intractable to scientific inquiry – perhaps due to the vague concepts applied to the field of research. One attempt to limit the purview of creative cognition formulates the construct in terms of evolutionary constraints, namely that of blind variation and selective retention (BVSR). Behaviorally, one can limit the “blind variation” component to idea generation tests as manifested by measures of divergent thinking. The “selective retention” component can be represented by measures of convergent thinking, as represented by measures of remote associates. We summarize results from measures of creative cognition, correlated with structural neuroimaging measures including structural magnetic resonance imaging (sMRI), Diffusion Tensor Imaging (DTI), and proton magnetic resonance imaging (1H-MRS). We also review lesion studies, considered to be the “gold standard” of brain-behavioral studies. What emerges is a picture consistent with theories of disinhibitory brain features subserving creative cognition, as described previously (Martindale, 1981). We provide a perspective, involving aspects of the default mode network, which might provide a “first approximation” regarding how creative cognition might map on to the human brain.